Chemically Recyclable CO2‐Based Solid Polyesters with Facile Property Tunability. Issue 20 (8th June 2022) - Lou, Yongjia; Xu, Jialin; Xu, Luyan; Chen, Zhuo; Lin, Bo‐Lin
Abstract: Synthesizing chemically recyclable solid polymeric materials is a significant strategy to potentially achieve carbon neutral production of new polymers and alleviate plastic pollution, especially when the synthesis is based on CO2 and inexpensive co‐feedstocks available in large scales. Additionally, polymeric materials should have high enough molecular weight to exhibit distinguished properties from low molar mass polymers to serve for a broader range of application scenarios. However, up to now, strategies for developing solid‐state CO2 ‐based chemically recyclable polyesters with both high molecular weight and facile property tunability are still unprecedented. Herein, a brand‐new synthetic route is developed to synthesize chemically recyclable CO2 ‐based solid polyesters with high molecular weight ( M n up to 587.7 kg mol −1 ) and narrow dispersity ( Đ < 1.2), which should further broaden the potential application scenarios of new CO2 ‐based polyesters. Additionally, complete monomer recovery from poly(δLH2 ) material is also achieved. The preserved terminal alkene groups allow facile property tuning of the polyesters via photo‐initiated thiol‐ene click reactions, enabling more potential utilities and further functionalizations. Abstract : A brand‐new stepwise synthetic route to make completely chemically recyclable CO2 ‐based solid polyesters with high molecular weight and tunable properties from CO2 and 1, 3‐butadiene is disclosed. High‐CO2 ‐content, transparent polyesters with high molecular weight is achieved. The preserved terminal olefins allow for facile property tuning capability of the polyesters through thiol‐ene click reactions, which enables more utilities of chemically recyclable polyesters.